Dysglycemia and long‐term mortality: observations from the Israel study of glucose intolerance, obesity and hypertension. Issue 4 (12th December 2014) - Bergman, Michael; Chetrit, Angela; Roth, Jesse; Dankner, Rachel
Abstract: Background: We describe the relationship between dysglycemia and long‐term mortality and elucidate the relationship between blood glucose levels during an oral glucose tolerance test (OGTT) and haemoglobin A1 (HbA1) and mortality. Methods: A cohort of 1410 individuals was followed for 33 years since 1980. Fasting and post‐OGTT glucose parameters were used to categorize the cohort according to baseline glycemic status. Results: The mortality rate increased from 43% in normoglycemic individuals to 53.3, 61.7, 72.9 and 88.0% in those with impaired fasting glucose (IFG), impaired glucose tolerance (IGT), IFG/IGT and diabetes, respectively. The highest mortality rate, compared with the normoglycemic category, was observed in individuals with IFG/IGT and diabetes according to a Cox proportional hazard model (HR = 1.38, 95%CI 1.10–1.74 and HR = 2.14, 95%CI 1.70–2.70, respectively), followed by individuals with IGT and IFG, but this did not reach statistical significance. We speculate that the IFG group may represent a mixture of individuals en route from normal to the next two categories as well as another cohort whose glucose levels are stably set at the upper reaches of the normal distribution. Significant differences were found between 1 and 2 h glucose values ( p < 0.001). Fasting, 60 and 120 min glucose values were positively associated with increasing HbA1 quintiles ( p < 0.05). The mean HbA1 was significantly higher in those who died ( p = 0.01). The highest mortality (58.8%) was observed in the upper HbA1 quintile that was also associated with the highest prevalence of the metabolic syndrome (17.2%). Conclusions: This study shows a continuous relationship between the severity of dysglycemia and long‐term mortality and should promote the early recognition of prediabetes. The 1 h post‐load glucose level was continuously associated with increasing HbA1 concentrations and may therefore serve as an early marker for abnormalities in glucose tolerance. An elevated 1 h post‐load glucose level may potentially identify at‐risk individuals well before the traditional 2 h glucose value. Copyright © 2014 John Wiley & Sons, Ltd.